CURRENT TRENDS IN PUBLISHING IN DENTISTRY - Cristina Teodora Preoteasa; Elena Preoteasa (Romanian Society of Oral Rehabilitation, 2017)
This study aimed to observe the current trends in publishing in the scientific literature in dentistry. Articles from the highest 10 ranked journals from the category of Dentistry, Oral Surgery & Medicine, of Science Citation Index Expanded (SCIE) of Thomson Reuters were analyzed in regard to the topics addressed, and as research methodology. This study results suggest that, the publishing trend is characterized by dominance of original researches, from which most are clinical studies. Regarding the latter, there can be noticed that a great variety of study designs were reported, most of them being cross-sectional studies, cohort study, case reports and case series, a long follow-up period being found especially in cohort studies, an important part of them being conducted on large sample size. Most of the articles addressed topics related to therapy, and were in the field of Implant dentistry. The great variety of article, as designs and topics addressed, can be regarded as positive facts identified, even so, it is desired to observe an increase publication of the studies that have a high level of evidence, namely reporting randomized controlled trials and systematic reviews.